Error and the growth of experimental knowledge - Mayo, Deborah G (University of Chicago press, Chicago, 1996)
Deborah Mayo's "Error and the Growth of Experimental Knowledge" offers a compelling critique of subjective Bayesianism and proposes an error-statistical approach as a more reliable framework for understanding scientific inquiry. Mayo's focus on error correction and severe testing provides a robust methodology for evaluating hypotheses and drawing reliable conclusions. The book delves into the philosophical foundations of scientific knowledge, challenging conventional wisdom and offering a fresh perspective. It provides practical guidance for researchers, particularly those working with statistical analysis, while also engaging with broader epistemological questions. Mayo's work is a valuable contribution to the philosophy of science, offering a rigorous and insightful exploration of the nature of scientific inquiry.
Includes bibliographical references (p. 465-480) and index.
Keywords: Error statistics; Severe testing; Epistemology of experiment; Bayesian inference; Philosophical foundations of science; Scientific method; Statistical inference; Model selection; Data analysis